2021
DOI: 10.1016/j.ultrasmedbio.2020.12.022
|View full text |Cite
|
Sign up to set email alerts
|

Indexing Cerebrovascular Health Using Transcranial Doppler Ultrasound

Abstract: Transcranial Doppler (TCD) blood flow velocity has been extensively used in biomedical research as it provides a cost-effective and relatively simple approach to assess changes in cerebral blood flow dynamics and track cerebrovascular health status. In this paper, we introduce a new TCD based timing index, TI TCD , as an indicator of vascular stiffening and vascular health. We investigate the correlations of the new index and the existing indices, namely the pulsatility index (PI TCD ) and the augmentation ind… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…While no previous NiRS studies have reported a timing index, the correlations of with age and CRF match those of the TCD reported by our group 20 . That is, correlations of and between TCD TI and age in two different datasets and a correlation of between TCD TI and CRF.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…While no previous NiRS studies have reported a timing index, the correlations of with age and CRF match those of the TCD reported by our group 20 . That is, correlations of and between TCD TI and age in two different datasets and a correlation of between TCD TI and CRF.…”
Section: Discussionsupporting
confidence: 87%
“…All experiments were performed in accordance with relevant guidelines and regulations. TCD recordings from these participants were previously reported in 20 . Each participant attended the Hunter Medical Research Institute and the University of Newcastle Callaghan campus over two consecutive days and participated in three scanning sessions.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The proposed model for T refl and AI can facilitate studies of vascular ageing by providing means to understand how changes is vascular properties such as R and C are reflected in these indices [40].…”
Section: Discussionmentioning
confidence: 99%